Composite, hybrid, and multifunctional materials, volume 4 proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics - Annual Conference on Experimental and Applied Mechanics Greenville, S.C.) (2014; Tandon, Gyaneshwar; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
Experimental Mechanics of Composite, Hybrid, and Multifunctional Materials, Volume 4: Proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics, the fourth volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Composites for Energy Applications Novel/Bio Composites NDE of Composites Mechanical Testing of Composites Strain Measurements Using Digital Image Correlation Digital Image Correlation for Composite Structures Particulate Composites Nanocomposites
Electronic reproduction.
Keywords: Mechanics, Applied -- Congresses; Materials; Surfaces (Physics).; Electronic books